The Causes and Long-Term Consequences of Viral Encephalitis - Bohmwald, Karen; Andrade, Catalina A.; Gálvez, Nicolás M. S.; Mora, Valentina P.; Muñoz, José T.; Kalergis, Alexis M. (Frontiers in Cellular Neuroscience, 2021)
Reports showing inflammation of the brain, known as encephalitis, have shown an increasing frequency during the past years. Encephalitis is relevant in public health due to high morbidity and mortality. Infectious or autoimmune diseases are the most common cause of encephalitis. The clinical symptoms of this pathology can vary depending on the brain zone affected, with mild ones such as fever, headache, confusion, and stiff neck, or severe ones, such as seizures, weakness, hallucinations, and coma, among others. Encephalitis can affect individuals of all ages, but it is frequently observed in the pediatric and elderly population, and the most common causes are viral infections. Several viral agents have been described as agents leading to encephalitis, including arboviruses, enteroviruses, herpesviruses, retroviruses, orthomyxoviruses, orthopneumovirus, and coronaviruses, among others. Once a neurotropic virus reaches the brain parenchyma, the resident cells such as neurons, astrocytes, and microglia, can be infected, promoting the secretion of pro-inflammatory molecules and the subsequent immune cell infiltration that leads to brain damage. After the resolution of the viral infection, the local immune response can remain active, which may contribute to long-term neuropsychiatric disorders, neurocognitive impairment, and degenerative diseases. In this article, we will discuss how viruses can reach the brain, the impact of viral encephalitis on brain function, and we will also special focus on the neurocognitive sequelae reported even after viruses are cleared.